Analisis Metode Hermeneutika Kitab Suci dalam Tradisi Gereja Ortodoks Timur - Tjong, Andrew Lucas (Student Evangelical Journal Aiming At Theological Interpretation, 2025)
This article aims to elucidate the principles and approaches of hermeneutics within the Eastern Orthodox Church tradition through a library research method that examines the documents and literature of the Eastern Orthodox Church. The hermeneutical method of the Eastern Orthodox Church emphasizes communal interpretation, the unity of Holy Scripture with Holy Tradition, the role of the Holy Spirit in interpretation, the continuity of apostolic succession, and an orientation toward the spiritual transformation of the faithful. The approaches employed include the Christological-Pneumatological, ecclesiological and patristic, literal, allegorical-typological, ethical, moral and spiritual, ascetic, as well as liturgical and iconographic approaches. Collectively, these approaches demonstrate that Eastern Orthodox hermeneutics is inseparable from the life of the Church and aims to lead the faithful toward theosis, the union with God. This article affirms that, in the Eastern Orthodox Church, Holy Scripture is understood holistically as the living Word, interpreted in the light of the Church’s faith, and lived out in the spiritual life of the faithful.